Li2MnO3/LiMnBO3/MnFe2O4 ternary nanocomposites: Pechini synthesis, characterization and photocatalytic performance. (21st August 2020) - Ranjeh, Mahdi; Masjedi-Arani, Maryam; Amiri, Omid; Salavati-Niasari, Masoud
Abstract: Li2 MnO3 /LiMnBO3 /MnFe2 O4 ternary nanocomposites were synthesized via modified pechini sol-gel approach employing the mixture of metal cations, boric acid, ethylene glycol and ethylene diamine tetra acetic acid gelating agent. Shape and size of nanocomposites was controlled by changing molar ratio of metal ions, ethylene glycol and gelating agent. In order to confirmation of crystalline and structural features of products, analyses of X-ray diffraction, Fourier transform infrared and energy dispersive X-ray were carried out. Scanning electron microscopy and transmission electron microscopy images were taken for morphology investigation of nanostructure products. Band-gap of ternary nanocomposites calculated by UV–Vis data is 2.6 eV. Magnetic property of Li2 MnO3 /LiMnBO3 /MnFe2 O4 ternary nanocomposites investigated through vibrating sample magnetometer presents ferromagnetic behavior. Moreover, photocatalytic activity of Li2 MnO3 /LiMnBO3 /MnFe2 O4 and Li2 MnO3 /LiMnBO3 nanocomposites was investigated in aqueous solution via UV and visible light for degradation acid red 88 dye. Some effective parameters such as dye concentration, irradiation and nanocomposite type were evaluated for optimum removal of water pollutant dye. Highlights: LLM ternary were synthesized via modified pechini sol-gel approach. Effect of different experimental factors was considered. The photocatalytic activity of prepared LLM ternary as investigated. Divers parameters were evaluated in order to higher photocatalytic efficiency.